2020
DOI: 10.1109/access.2020.2994219
|View full text |Cite
|
Sign up to set email alerts
|

Subsynchronous Oscillation Analysis of Grid-Connected Converter Based on MIMO Transfer Functions

Abstract: Subsynchronous oscillations (SSOs) induced by the interaction between wind farms based on direct-drive permanent magnet synchronous generators (D-PMSGs) and weak grids have attracted extensive attention. To better understand this SSO phenomenon, this paper derives multi-input multi-output (MIMO) transfer functions between the references of the current controller and the current of a grid-connected converter in the d-q frame, where the dynamic of PLL is considered. The dynamic of PLL lead to positive feedback i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…For current-type VSCs, the slow-interaction converter-driven instability is mainly due to the asymmetrical PLL dynamics, 5 i.e., only regulating q-axis PCC voltage introducing positive feedback into the system [58][59][60]. By examining the closed-loop poles of current-type VSCs, it is found that there is one pair of complex poles (P1,2) that have the low-frequency dynamics related to system fundamental frequency sideband oscillations [58]. The root-locus approach is applied to analyze the locations of the poles to study the impact of the PLL (proportional gain Kpll_P and integral gain Kpll_I) as shown in Fig.…”
Section: ) Pll Controlmentioning
confidence: 99%
“…For current-type VSCs, the slow-interaction converter-driven instability is mainly due to the asymmetrical PLL dynamics, 5 i.e., only regulating q-axis PCC voltage introducing positive feedback into the system [58][59][60]. By examining the closed-loop poles of current-type VSCs, it is found that there is one pair of complex poles (P1,2) that have the low-frequency dynamics related to system fundamental frequency sideband oscillations [58]. The root-locus approach is applied to analyze the locations of the poles to study the impact of the PLL (proportional gain Kpll_P and integral gain Kpll_I) as shown in Fig.…”
Section: ) Pll Controlmentioning
confidence: 99%